Assessing soil P fractions changes with long-term phosphorus fertilization related to crop yield of soybean and maize - Appelhans, Stefania Carolina (2020)
Long-term P Fertiliser application increases soil phosphorus (P) labile fractions, which can be associated with crop P uptake and grain yield and are useful to improve fertilizer recommendations. Research aims were to evaluate in long-term experiments with different P Fertiliser application in a Mollisol and a Vertisol: (a) the changes of soil P fractions and (b) the relationship between soil P fractions with long-term P Fertiliser application, with accumulated apparent P budget, grain P, total P uptake, soybean (Glycine max L.Merr.) and maize (Zea mays L.) grain yield. Soil P fractions were measured after 1 and 9 year since the beginning of the long-term experiments. Experiments included an initial Fertiliser application rate of 200 kg P ha−1 and annual P Fertiliser application rate of 36 kg P ha−1. Bray1-P, total, organic, and inorganic P in fine (<53 μm) and coarse (>53 μm) (CF) soil fractions, and in NaHCO3 extract were measured. Initial P Fertiliser application increased inorganic and total P fractions. However, Bray1-P, total P in NaHCO3 extract and in the CF were the fractions that most increased with continuous long-term P Fertiliser application in both sites. In the Mollisol, maize grain yield was unrelated to long-term P Fertiliser application. In the Vertisol, total P in NaHCO3 extract, and total and organic P in the CF were more closely related to soybean grain yield than Bray1-P. We proposed soil P indices of labile inorganic and organic P that showed close relationships with soybean grain yield and may be useful to improve the diagnosis of P soil fertility.